INTEGRASI NILAI-NILAI ISLAM DALAM PENGEMBANGAN ILMU PENGETAHUAN PADA ERA SOCIETY 5.0 - Fakhri Muhammad Ario Putra; Al Anshari; Irmawati Irmawati (Taksasila Edukasi Insani, 2025)
This study examines the integration of Islamic values in the development of science and technology in the Society 5.0 era through a qualitative literature study. The research analyzes three main aspects: (1) the concept of tadabbur alam (contemplation of nature) in the Qur'an as an epistemological foundation, (2) critique of secular science from a tawhidic paradigm perspective, and (3) implementation models in Islamic higher education. Findings reveal that the Qur'an provides a comprehensive epistemological framework connecting empirical observation, rational reasoning, and spiritual internalization. Case studies at UIN Bandung and UIN Surabaya demonstrate successful curriculum integration models such as